Prosthetics - Huddleston, Emma (Engineering the human body., 2020)
Investigates the power of modern prosthetics to aid and improve the lives of people with missing limbs. Discusses new technology that has made prosthetic devices more effective, useful, and discreet than ever. Includes a glossary.